Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1590/s1677-5538.ibju.2021.0475
|View full text |Cite
|
Sign up to set email alerts
|

Single-use flexible ureteroscopes: update and perspective in developing countries. A narrative review

Abstract: Flexible ureteroscopy is a well-established method for treatment of urinary stones but fl exible ureteroscopes are expensive and fragile devices with a very limited lifetime. Since 2006 with the advent of digital fl exible ureteroscopes a great evolution has occurred. The fi rst single-use fl exible ureteroscope was launched in 2011 and new models are coming to the market. The aim of this article is to review the characteristics of these devices, compare their results with the reusable devices and evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…In their article, Mazzucchi et al perfectly show different situations where we observe advantages and disadvantages of using each type of device and the different results found by different authors (1).…”
Section: Conflict Of Interestmentioning
confidence: 60%
“…In their article, Mazzucchi et al perfectly show different situations where we observe advantages and disadvantages of using each type of device and the different results found by different authors (1).…”
Section: Conflict Of Interestmentioning
confidence: 60%
“…The key gamechangers related to RIRS evolution include the development of disposable ureteroscopes and the new Thulium fiber laser (TFL). Single-use devices offer some advantages over the reusable flexible ureteroscopes: they are lighter (which may prevent fatigue in long lasting cases especially when treating large burden stones), offer a better deflection angle and provide superior image quality ( 7 ). Other authors also observed single-use device was associated with shorter operative time and higher stone free rates with possibly less complications ( 8 10 ).…”
Section: Commentmentioning
confidence: 99%
“…Other authors also observed single-use device was associated with shorter operative time and higher stone free rates with possibly less complications ( 8 10 ). Moreover, the use of disposable material may reduce total costs to the health care system, which is vital within developing countries perspectives, including Brazil ( 7 ). Current literature on TFL provides compelling results when compared to Holmium laser, indicating it is a milestone in RIRS: higher stone ablation rate (2 to 4 times faster), less calculi retropulsion and more efficient fragmentation generating smaller fragments.…”
Section: Commentmentioning
confidence: 99%
“…With the development of minimally invasive technology, Basiri et al (15)(16)(17)(18) reported that ureteroscopic incision and internal drainage were used to treat parapelvic cysts. In 1991, Kavoussi et al (19) reported that they successfully performed ureteroscopic incision and internal drainage by ureteroscopy.…”
Section: Figure 2 -The Left Parapelvic Cyst Was Identified By Injecti...mentioning
confidence: 99%